Overview on key technology and solution of C-V2X for internet of vehicles - Zhenjiang DONG; Yongcheng GU; Jian LIANG; Zhenjiang HUANG; Jie WANG; Dacheng LI (Dianxin kexue)
C-V2X is regarded as one of the most promising applications of 5G.Firstly,the necessity and the technical problems in the construction of the integration development of intelligent driving and C-V2X were introduced.Then,combined with the total solution of V2X,the functional positioning,key technology trends,problems and product morphology of each network element were studied.Typical internet of vehicles services were combed out and a typical service sequence flow diagram was presented.Finally,the key technologies in the future development of internet of vehicles were prospected.